Pelatihan Pengolahan Limbah Pertanian dan Peternakan Pada Masyarakat Tani Ternak di Desa Tete Batu Kecamatan Sikur Kabupaten Lombok Timur - Dwi Kusuma Permatasari; Syamsuhaidi Syamsuhaidi; Tjokorda S. Binetra; Pardi Pardi; Sumiati Sumiati; S. Sulastri (Universitas Mataram, 2020)
This activity is based on potensial of Tete Batu Village as agricultural area so that the availability of agricultural waste is abundant and so far it has not been used optimally as animal feed. Community service activities are carried out by providing materials on the technology of processing agricultural waste using various fermenters and local feed ingredients that can be used as alternative feed ingredients, then continuing the practice of processing livestock waste into liquid organic ferlizer and processing agricultural waste into silage. The service activity was attended by the Lombok Regional Government which involved in fostering livestock, head and management of Tete Batu, the livestock farming community, alumni and student, avarage 40 people. The community service activities have succeeded in increasing the knowledge and skills of breeders in processing livestock waste into liquid organic ferlizer which can be used to increase the fertility of agricultural plants and become products that can be sold so as to increase the income of the livestock farming community. Community service activities have resulted in good commitment from the livestock farming community, village administrators and related local government agencies to assist livestock farming communities in processing agricultural and livestock waste into useful products.